2018
DOI: 10.1212/wnl.0000000000006439
|View full text |Cite|
|
Sign up to set email alerts
|

Novel biomarker signatures for idiopathic REM sleep behavior disorder

Abstract: ObjectiveTo perform a rigorous in-depth proteomics analysis to identify circulating biomarker signatures for idiopathic REM sleep behavior disorder (RBD), capable of providing new insights into the underlying pathogenic mechanisms and putative α-synuclein-related neurodegenerative processes.MethodsSerum samples from patients with idiopathic RBD (n = 9) and healthy controls (n = 10) were subjected to a thorough liquid chromatography–mass spectrometry (MS)/MS proteomics analysis using ultimate 3,000 nanoLC inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
2
19
1
Order By: Relevance
“…This corresponds to other studies after sleep deprivation (Becker et al, 2014;Liu et al, 2009). This protein has also been shown in a novel proteomic study in idiopathic REM sleep behavior disorder to be differentially expressed (Mondello et al, 2018). It has been indicated to play a crucial role in regulating important physiological functions including complement activation, blood coagulation (FXIIa inhibitor), fibrinolysis and the generation of kinins.…”
Section: Downregulated Proteins In All Subjectssupporting
confidence: 80%
See 1 more Smart Citation
“…This corresponds to other studies after sleep deprivation (Becker et al, 2014;Liu et al, 2009). This protein has also been shown in a novel proteomic study in idiopathic REM sleep behavior disorder to be differentially expressed (Mondello et al, 2018). It has been indicated to play a crucial role in regulating important physiological functions including complement activation, blood coagulation (FXIIa inhibitor), fibrinolysis and the generation of kinins.…”
Section: Downregulated Proteins In All Subjectssupporting
confidence: 80%
“…PTPRG is a signaling molecule regarding cellular processes including differentiation, mitotic cycle, and oncogenic transformation (Cheung et al, 2015). This protein has been shown in a novel proteomic study in idiopathic REM sleep disorder to be differentially expressed (Mondello et al, 2018). A reduction in PTPRG might have a function in negative regulation of neuronal projection (Baker et al, 2000).…”
Section: Downregulated Proteins In All Subjectsmentioning
confidence: 99%
“…However, this finding may simply reflect compensation against certain types of inflammatory processes, such as α‐synuclein accumulation. In contrast to our findings, a recent study showed that serum C‐reactive protein, which is another proinflammatory marker, was significantly upregulated in iRBD patients compared to healthy controls . However, this result was obtained from only 9 iRBD patients, and thus firm conclusions cannot be drawn.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with this, inflammatory biomarkers were recently examined in studies of Rapid Eye Movement (REM) Behavior Disorder (RBD) patients. 75,76 There is some circumstantial evidence from studies of blood cytokines, which suggest that these are higher in early disease and decline with time, 77 as well as some evidence that blood lymphocytes recognizing α-synuclein antigens can be detected early. Stokholm et al 78 have observed increased PK 11195 binding in subjects with RBD.…”
Section: Question 8: When Does Inflammation Begin In Pd?mentioning
confidence: 99%